2022
DOI: 10.3389/fpubh.2022.851740
|View full text |Cite
|
Sign up to set email alerts
|

Price Policy and Taxation as Effective Strategies for Tobacco Control

Abstract: ObjectiveOnly 13% of the world's population are living in countries imposing appropriate tobacco tax-rates. This study aims to promote the implementation of price policy measures as a striking tobacco control strategy in Austria and to encourage other countries to further increase their taxes to WHO best-practice levels.MethodThis study used the yearly economic data from Austria from 1997 to 2015. Applying a model for regression analysis, the price elasticity of total tobacco consumption was estimated.ResultsB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The large percentage of smokers who were classified as price-sensitive contributes to the evidence pointing out that a tobacco taxation increase in Vietnam might be effective in decreasing smoking prevalence. Price increases and higher taxation are cost-effective ways to both reduce cigarette consumption among current smokers and discourage smoking initiation among non-smokers [19][20][21] . A previous study confirmed that a 10% increase in cigarette price would decrease consumption by around 1% in Vietnam, reducing the number of male smokers by approximately 270 thousand 22 .…”
Section: Discussionmentioning
confidence: 99%
“…The large percentage of smokers who were classified as price-sensitive contributes to the evidence pointing out that a tobacco taxation increase in Vietnam might be effective in decreasing smoking prevalence. Price increases and higher taxation are cost-effective ways to both reduce cigarette consumption among current smokers and discourage smoking initiation among non-smokers [19][20][21] . A previous study confirmed that a 10% increase in cigarette price would decrease consumption by around 1% in Vietnam, reducing the number of male smokers by approximately 270 thousand 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, price policy and taxation are effective strategies to reduce tobacco consumption and especially to prevent smoking initiation among adolescents (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, from a Public Health perspective, measures should increasingly focus on smoking behaviors of female adolescents and should endeavor to continue the recently observed decline of smoking prevalence among women in Austria. Particularly, price policy and taxation are effective strategies to reduce tobacco consumption and especially to prevent smoking initiation among adolescents ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing tobacco taxation is an efficient tool for its control. However, only 13 % of the global population lives in countries that impose adequate taxation on tobacco (Felsinger, Groman, 2022). Olesinski, Rozkrut, Toroj (2020) state that the differences between the actual and optimal tax policy in the case of tobacco products were marginal in the Polish market in the period 2014-2018.…”
Section: Literature Reviewmentioning
confidence: 99%